Reward Optimisation: The case for employer branding - Horn, Johan Andries (Organisational Psychology, 2019)
Orientation In competitive global markets, it is becoming ever-more challenging to attract and retain talented employees that possess scarce skills critical to the sustained success of an organisation. Technological advancement and the changing nature of the work has exponentially increased the demand for highly skilled knowledge workers, often referred to simply as talent. Imitating the products and processes of competitors has become easier to do than ever before and competitive advantage is increasingly being found in intangible assets, such as a reputable/desirable employer brand and having access to scarce intellectual and human capital. Reason for the Study A positive relationship between the level of remuneration and the perceived attractiveness of a job offer has consistently been found and is often the basis of determining reward offerings. The global economic recession of the recent past and the decreasing availability of financial resources has meant that organisations need to identify alternative (non-financial) strategies to attract, motivate and retain employees, colloquially referred to as the war for talent. Developing a desirable and attractive employer brand has become a promising non-financial strategy that has already proven to be effective in talent attraction and retention. In the present study, the notion that talented employees may accept a lower level of remuneration to be employed at an organisation that is perceived to have a reputable/desirable employer brand was investigated, in other words that a reputable/desirable employer brand may represent a remuneration discount for organisations. Given that remuneration or the salary bill is typically the largest expense for any organisation and provided the offers remain attractive to talented employees, any saving will represent a significant amount of money. Attracting talented employees, at a remuneration discount compared to their competitors, would enable organisations to further enhance their competitive advantage and increase their sustainability in an economy characterised by limited financial resources. Research Purpose In a similar manner as consumers are willing to pay a premium or inflated price for a product that has a desirable brand, it was argued in the present study that knowledge workers may accept a lower level of remuneration to be employed at an organisation that is perceived by them to have a reputable/desirable employer brand. The aim of the study was, therefore, to investigate if a reputable/desirable employer brand could result in a remuneration discount for organisations, while still achieving similar levels of job attractiveness amongst prospective employees. Research Design The present study employed a 2x2 or 22 full-factorial experimental design. Two independent variables were manipulated, namely remuneration well-above the industry norm (present or not present) and a reputable/desirable employer brand (present or not present) resulting in four distinct conditions. Perceived job attractiveness (the dependent variable) was measured after a respondent was exposed to one of the four stimulus conditions. The variables were manipulated by offering respondents one of four job advertisements, each being the same other than differing in terms of the manipulations. The job advertisements were used as a stimulus to determine the effect of remuneration and employer brand on perceived job attractiveness, as well as to investigate if any interaction effects were present. Furthermore, respondents were asked to estimate their expected salary per annum for the job advertisement (stimulus condition) they were exposed to. The expected salary that participants estimated when exposed to a job advertisement was considered a measure of brand equity. Respondents were additionally presented with an employer brand survey containing different brand images. Respondents were asked open-ended questions based on the brands they were exposed to. Examples of the questions included “Considering the brands illustrated above, which of them would you consider your dream job?” and “Would you be willing to accept a remuneration discount to work at your dream job?” A non-probability convenience sampling approach was employed to distribute an online survey to different organisations and individuals across South African organisations. Approximately 180 questionnaires were distributed, of which 161 questionnaires were returned. A realised sample (n = 121) was achieved once responses with more than 20% missing data were removed. As a snow-balling approach was further used, one is not able to calculate a response rate. Random assignment of respondents (i.e. randomisation) was achieved by setting the Qualtrics software to randomly assign each respondent to one of the four experimental conditions (i.e. one of the four job advertisements). This was done to ensure that the four sub-samples of respondents, in other words in each of the four conditions were similar and not different in any respect other than the stimulus they were exposed to, so ensuring the validity of the results. Data was analysed using Descriptive Statistics, Principal Components Analysis and a Full-Factorial ANOVA.